Effect of Sodium Hydroxyde (NaOH) and Sodium Hypochlorite (NaHClO) on Morphology and Mineral Concentration of Zea mays Hairs (cornsilk) - Wan Rosli, W. I.; Nurhanan, A. R.; Farid, C. G.; Mohsin, S. S. J. (Microscopy Society of Singapore, 2010)
Prehistoric and ancient civilizations have long relied on dietary minerals in the prevention of diseases. Major minerals serve as structural components of tissues, function in cellular and basal metabolism, and in water and acid-base balance. This study is discussing on the effect of NaOH and NaHClO on morphology and mineral concentration of cornsilk. A smear layer like soft gelatinous adherent covering the uppermost part of the NaOH treated cornsilk while the cornsilk treated by NaHClO was filled with various features of grape-like globules. The amounts of Ca, K, Mg, Mn and Zn in fresh and oven dried cornsilk were comparatively higher than in samples treated with NaOH and NaHClO. The concentration of Ca in fresh and oven dried cornsilk was accounted for 546 and 323 mg/L, respectively and higher than the concentration of cornsilks macerated with NaOH (108 mg/L) and NaHClO (7.6 mg/L). Both cornsilk treated with NaOH and NaHClO recorded the highest concentration of Na (30533 and 60200 mg/L, respectively). In conclusion, NaOH and NaHClO were detrimentally and distorted natural cytoskeleton of the tissues by removing essential organic and inorganic components. The highest mineral contents presented in fresh and oven dried cornsilk were Ca, K, Mg, Mn and Zn.